Design of a mobile shared test cabinet of auxiliaries controller. Issue 6 (April 2019) - Zhang, Qingyong; Zou, Shaowei; Wang, Yaru; Lu, Zhenfei; Lin, Weiping
Abstract: The test parts in the split state of auxiliaries controller used for pure electric bus exists some problems. This paper designs the auxiliary controller through electrical principle design, test cabinet structure design and so on. Through static analysis, simulation of the actual load is performed to verify the strength of the cabinet and the reliability of the design. Finally the design of a mobile shared test cabinet of vehicle auxiliaries controller is completed. The design of the test cabinet improves the layout of test parts for auxiliary controller, achieves mobile testing, and completes the integration of the corresponding functions. It can save space, clarify function division and store goods, which reduces the burden of testers and make testing easy and simple. It also can reduce operator connection error rate and greatly improve testing efficiency.